Microbial communities inhabiting shallow hydrothermal vents as sentinels of acidification processes - Arcadi, Erika; Rizzo, Carmen; Calogero, Rosario; Sciutteri, Valentina; Fabiano, Francesco; Consoli, Pierpaolo; Andaloro, Franco; Romeo, Teresa (Frontiers in Microbiology, 2023)
Shallow hydrothermal vents are considered natural laboratories to study the effects of acidification on biota, due to the consistent CO2 emissions with a consequent decrease in the local pH. Here the microbial communities of water and sediment samples from Levante Bay (Vulcano Island) with different pH and redox conditions were explored by Next Generation Sequencing techniques. The taxonomic structure was elucidated and compared with previous studies from the same area in the last decades.The results revealed substantial shifts in the taxonomic structure of both bacterial and archaeal communities, with special relevance in the sediment samples, where the effects of external ha eliminato: Calogero 1